Different central nervous system cell types display distinct and nonrandom arrangements of satellite DNA sequences. - Manuelidis, L (1984)
Paraformaldehyde-fixed tissue from mouse cerebellum was hybridized with biotin-labeled satellite DNA for identification of centromeres. By using avidin-peroxidase conjugates, it was possible to define the nuclear position of centromeres at the ultrastructural level. Three-dimensional analysis of well-resolved centromere arrays were aided by computer reconstruction of serial sections. Different cell types displayed distinct, nonrandom centromere locations. In Purkinje neurons, the majority of detected sequences were clustered together around the central nucleolus, whereas in granule neurons, more numerous, dispersed centromere clusters were associated with the nuclear membrane. In Purkinje cells, peroxidase-labeled regions corresponded to dense heterochromatic aggregates were detected in Purkinje cells of several different species. These observations suggest that in these highly differentiated cells, the nuclear position of centromeres is maintained in evolution despite species differences in centromeric DNA sequence. Such defined ordering of centromeres may be integral to specific functional capacities.